Weakest preconditioned goto axiom - Chen, Wei (Information processing letters, 2023)
This paper presents an axiom for goto statements in terms of Dijkstra's weakest (liberal) precondition model. We give a detailed comparison of our axiom with Arbib and Alagic's approach and argue that the latter is actually flawed even if it offers a goto axiom that has widely been cited and adopted.